Evolution and targeting of Omp85 homologs in the chloroplast outer envelope membrane - Day, Philip M.; Potter, Daniel; Inoue, Kentaro (Frontiers in Plant Science, 2014)
Translocon at the outer-envelope-membrane of chloroplasts 75 (Toc75) is the core component of the chloroplast protein import machinery. It belongs to the Omp85 family whose members exist in various Gram-negative bacteria, mitochondria and chloroplasts of eukaryotes. Chloroplasts of Viridiplantae contain another Omp85 homolog called outer envelope protein 80 (OEP80), whose exact function is unknown. In addition, the Arabidopsis thaliana genome encodes truncated forms of Toc75 and OEP80. Multiple studies have shown a common origin of the Omp85 homologs of cyanobacteria and chloroplasts but their results about evolutionary relationships among cyanobacterial Omp85 (cyanoOmp85), Toc75 and OEP80 are inconsistent. The bipartite targeting sequence-dependent sorting of Toc75 has been demonstrated but the targeting mechanisms of other chloroplast Omp85 homologs remain largely unexplored. This study was aimed to address these unresolved issues in order to further our understanding of chloroplast evolution. Sequence alignments and recently determined structures of bacterial Omp85 homologs were used to predict structures of chloroplast Omp85 homologs. The results enabled us to identify amino acid residues that may indicate functional divergence of Toc75 from cyanoOmp85 and OEP80. Phylogenetic analyses using Omp85 homologs from various cyanobacteria and chloroplasts provided strong support for the grouping of Toc75 and OEP80 sister to cyanoOmp85. However, this support was diminished when the analysis included Omp85 homologs from other bacteria and mitochondria. Finally, results of import assays using isolated chloroplasts support outer membrane localization of OEP80tr and indicate that OEP80 may carry a cleavable targeting sequence.